The role of DXA bone density scans in the diagnosis and treatment of osteoporosis. Issue 982 (3rd August 2007) - Blake, Glen M; Fogelman, Ignac
Abstract : Dual energy x ray absorptiometry (DXA) scans to measure bone mineral density (BMD) at the spine and hip have an important role in the evaluation of individuals at risk of osteoporosis, and in helping clinicians advise patients about the appropriate use of antifracture treatment. Compared with alternative bone densitometry techniques, hip and spine DXA examinations have a number of advantages that include a consensus that BMD results can be interpreted using the World Health Organization T-score definition of osteoporosis, a proven ability to predict fracture risk, proven effectiveness at targeting antifracture therapies, and the ability to monitor response to treatment. This review discusses the evidence for these and other clinical aspects of DXA scanning, including its role in the new WHO algorithm for treating patients on the basis of their individual fracture risk.